Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Solve for [tex]c[/tex].

[tex]\[
\begin{array}{l}
6c + 14 = -5c + 4 + 9c \\
c = \square
\end{array}
\][/tex]


Sagot :

Sure, let's solve the equation step by step:

Given the equation:
[tex]\[ 6c + 14 = -5c + 4 + 9c \][/tex]

First, combine the terms involving [tex]\(c\)[/tex] on the right side:
[tex]\[ -5c + 9c = 4c \][/tex]
So, the equation simplifies to:
[tex]\[ 6c + 14 = 4c + 4 \][/tex]

Next, to combine like terms involving [tex]\(c\)[/tex], subtract [tex]\(4c\)[/tex] from both sides:
[tex]\[ 6c - 4c + 14 = 4c - 4c + 4 \][/tex]
This simplifies to:
[tex]\[ 2c + 14 = 4 \][/tex]

To isolate the term with [tex]\(c\)[/tex], subtract 14 from both sides:
[tex]\[ 2c + 14 - 14 = 4 - 14 \][/tex]
[tex]\[ 2c = -10 \][/tex]

Finally, divide both sides by 2 to solve for [tex]\(c\)[/tex]:
[tex]\[ c = \frac{-10}{2} \][/tex]
[tex]\[ c = -5 \][/tex]

Therefore, the solution is:
[tex]\[ c = -5 \][/tex]